Characterization of a low-grade copper-sulphide ore to assess its suitability for in situ recovery. (30th January 2018) - Li, Jian; Kuhar, Laura; Austin, Peter; Da Costa, Micheal
Abstract : CSIRO Minerals is developing new technologies and approaches for the in situ recovery (ISR) of valuable metals. ISR provides opportunities to process small and/or deep deposits and could create additional revenue for conventional uneconomic mines. Unlike for conventional processing, no standard methodology exists for characterizing sample suitability for ISR. The authors are developing a workflow to understand sample and deposit amenability to ISR processing. A South Australian low-grade iron-oxide-copper-gold sulphide ore was studied. A total of 37 drill cores samples were obtained from the ore sample for detailed mineralogical and leaching characterization. A range of characterization techniques including chemical analysis, X-ray fluorescence mapping, quantitative evaluation of minerals by scanning electron microscopy, computed tomography scanning, and bulk- and micro-X-ray diffraction analyses were applied to understand the ore mineralogy. Leaching tests at 50 °C were performed on selected samples to understanding their leaching behaviour. Mineralogical characterization found that copper was present mostly as discrete secondary copper sulphides distributed in various areas and at various specimen depths, which, in theory should be readily available for leaching, provided sufficient solution access exists. Leaching results showed steady copper recovery under the conditions tested. This study provides insight into understanding the suitability of an ore for ISR processing.